Does teaching children about human rights, encourage them to practice, protect and promote the rights of others?. Issue 1 (2nd January 2018) - Dunhill, Ally
ABSTRACT: The purpose of the article is to demonstrate how the United Nations International Children's Emergency Fund (UNICEF) Rights Respecting Schools Award makes positive contributions to children's lives and experiences at school. Within the overall context of education as a right, the Award supports children to learn about their rights and the rights of others. By learning through a rights-based framework, children experience a rights-based approach to education and start to become active rights thinkers and rights holders. This article presents findings regarding the lived experiences of children participating in a rights education programme from a primary school in England. The results are consistent with previous rights education research and confirm that teaching and supporting the human rights of children to children, through a rights education programme, encourages children to practice, protect and promote the rights of others within their school.